Clostridium difficile spores: a major threat to the hospital environment. (April 2014) - Barra-Carrasco, Jonathan; Paredes-Sabja, Daniel
ABSTRACT: : Clostridium difficile is a Gram-positive, anaerobic spore former and is an important nosocomial and community-acquired pathogenic bacterium. C. difficile infections (CDI) are a leading cause of infections worldwide with elevated rates of morbidity. Despite the fact that two major virulence factors, the enterotoxin TcdA and the cytotoxin TcdB, are essential in the development of CDI, C. difficile spores are the main vehicle of infection, and persistence and transmission of CDI and are thought to play an essential role in episodes of CDI recurrence and horizontal transmission. Recent research has unmasked several properties of C. difficile's unique strategy to form highly transmissible spores and to persist in the colonic environment. Therefore, the aim of this article is to summarize recent advances in the biological properties of C. difficile spores, which might be clinically relevant to improve the management of CDI in hospital environments.